Iron(ii) spin crossover complexes with diaminonaphthalene-based Schiff base-like ligands: 1D coordination polymers. (29th March 2016) - Lochenie, Charles; Gebauer, Andreas; Klimm, Ottokar; Puchtler, Florian; Weber, Birgit
Abstract : Iron(ii ) spin crossover coordination polymers with diaminonaphthalene derived Schiff base-like ligands were synthesised, and their magnetic and structural properties were analysed. Rigid bridging ligands having up to 40 K wide hysteresis loops were observed. Abstract : The synthesis of iron(ii ) coordination polymers of new Schiff base-like ligands with an extended π-system is described. In total sixteen new compounds were synthesised. The complexes were characterised by X-ray powder diffraction and magnetic measurements. Four of these complexes remain in the low-spin state and six remain in the high-spin state in the entire temperature range investigated. The remaining six complexes show a spin crossover behaviour with a cooperative spin transition (28 and 40 K wide hysteresis loops) in two cases. The influence of the extended aromatic system on cooperative interactions is discussed.